Synthesis, structure and magnetic properties of a novel double layered brownmillerite Ca2LaFe1.75Cr0.25GaO8. (September 2020) - Dhal, Ramchandra; Neenu Lekshmi, P.; Das, Amitabh; Chatterji, Tapan; Sinha, Anil K.; Santhosh, P.N.
Graphical abstract: Rietveld refinement of NPD data (left) and the canted G-type AFM structure of Ca2 LaFe1.75 Cr0.25 GaO8 (right) at 4K. Highlights: Crystal and magnetic structure of Ca2 LaFe1.75 Cr0.25 GaO8 was studied thoroughly using synchrotron X-ray and neutron powder diffraction techniques. Compound possesses orthorhombic Pbma space group with tetrahedral chain ordering. ∼ 25% of Fe/Ga disorder between the Fe/Cr – octahedral and Ga –tetrahedral layers. Magnetic structure is found to be a canted G-type antiferromagnetic with weak FM component along crystallographic a -direction. Abstract: We report the structural and magnetic properties of a novel double layered Brownmillerite Ca2 LaFe1.75 Cr0.25 GaO8 . Synchrotron X-ray diffraction and neutron powder diffraction data confirms orthorhombic structure having Pbma space group with tetrahedral chain ordering and ∼ 25 % of cation (Fe/Ga) disorder between octahedral and tetrahedral sites. Ca2 LaFe1.75 Cr0.25 GaO8 exhibits antiferromagnetic transition at TN ∼630 K. The magnetic structure is determined as canted G-type antiferromagnetic with weak ferromagnetic component along a direction. The ordered magnetic moments obtained at 4 K are 2.24 (4) μB (Fe 3+ /Cr 3+ ) for octahedral sites and 2.34 (4) μB (Fe 3+ ) for tetrahedral sites.